The Concept of 'Doctorateness' and the Architecture of a PhD Thesis-from an Applied Linguistic Point of View - Zhang, Cheng (International Journal of Social Sciences and Public Administration, 2024)
The term 'doctorateness' is the nominalization of word 'doctorate' which is defined concisely as 'the highest degree awarded by the university'. The concept of 'doctorateness' has been discussed and developed by several experts whose analysis was conducted recently, providing a current perspective on the defining attributes of the concept. It can be defined as: Individual scholar, an apprenticeship process of development, original conceptual contribution, highest academic degree, stewardship of the discipline. This study can serve as a reference for building the framework in the Architecture of a PhD Thesis, and contribute to the understanding and development of the concept of doctorateness within the field of doctoral education.